PENDAMPINGAN DALAM MENGEMBANGKAN DAN MENENTUKAN IDE POKOK PARAGRAF SEBAGAI PERSIAPAN UN DI SMPIT DAN SMAIT YAPIDH - Ahmad Khoiril Anam; Fauzi Rahman; Ryan Hidayat (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
One of the problems in the low interest in learning Indonesian is the too long paragraphs of a discourse and the difficulty in determining the important elements in the paragraphs. In addition, the topics on a writing, sometimes become something that is very complicated to understand. From starting to determine the main sentence, main ideas, even the main ideas contained in a writing. To determine a main idea, it can be studied or reviewed from the material about paragraphs and its development. The problems that often arise are in the Indonesian National Examination questions, usually students have difficulty determining the main idea and main sentence and determining the theme of the entire paragraph. This ibM activity aims to provide an understanding of paragraph development and determine the main idea and main sentence in a paragraph as a form of preparation for the National Examination at SMPIT and SMAIT Yapidh. The methods used in this community service are lectures, questions, and answers with assignments. The results of the activity show the importance of understanding paragraph development and how to determine main ideas and main sentences in preparation for the National Examination. This is very helpful in increasing the confidence of students when facing the Computer-based National Examination. Because, by understanding and knowing the main idea of a paragraph correctly, students can find out the outline of the story and can conclude the contents of the paragraph appropriately.